UPAYA MENGATASI PERMASALAHAN JENDER DALAM PEMBANGUNAN - Suhita, Damayanti (Transformasi, 2015)
A gender sensitive development mesyaratkan active role human in all fields of development. Withthe issue of gender equal partnership may not be realized. Gender will hamper the pace ofdevelopment, because there will be no balance, harmony and harmony between men and womenSo that the active role of government and the need for more community members opportunitiesfor women in the field of social policy and development.Key Words : Gender issues, development